Multi-Leg Shear Reinforcement of Gfrp and Steel Lwrc Edge Column-Slab Connections: A Comparison Study - Saeed, Mustafa F.; Harba, Ibrahim S. I. (Communications - Scientific Letters of the University of Zilina, 2024)
The behaviour of lightweight concrete (LWC) edge column-slab connections reinforced with two types of flexural reinforcement glass fiber-reinforced polymer (GFRP) and steel bars with different ratios of shear reinforcement are investigated experimentally and analytically using ABAQUS software. The experimental protocol covered evaluation of eight slabs and edge columns measuring subjected to static loading. Slabs are evaluated as supported, free-standing at one edge, and the column connection is included. The slabs are divided into two groupings, with four slabs in each group. The first group was reinforced with steel flexural, while the second group was reinforced with GFRP reinforcement. Within each group, one slab lacked shear reinforcement, while the other was reinforced with a varying shear reinforcement ratio. A good agreement was found between the numerical FE model and experimental outcomes in most tested slabs.
Keywords: lightweight concrete; punching shear; edge column slab connection; GFRP; multi-leg shear reinforcement; LWC